Is it time for Peru to adopt the nine-valent vaccine? - Venegas Rodríguez, Gino (2024)
Cervical cancer remains a challenge worldwide, especially in middle- and low-resource countries. HPV vaccination is one of the most important weapons included in the WHO's goals for 2030. The need to use a single dose is increasingly acceptedin various national programs. The comparison of one, two, and three doses of HPVvaccines is very important to understand the changes occurring in the nationalpolicies of different countries. In Peru, the national vaccination program uses a singledose of the tetravalent vaccine from 9-18 years of age, gender-neutral.